Diagnostic dermoscopic features and the correlation between dermoscopic and histopathologic features in lichen planus - Jose, Sherin; Kurien, George (International Journal of Research in Dermatology, 2020)
Background: Lichen planus (LP) is an autoimmune dermatosis characterized by pruritic violaceous flat-topped polygonal papules predominantly over the extremities but can also affect trunk, mucosa, scalp, palms, soles and nails. Dermoscopy is a novel non-invasive imaging modality and the presence of salient dermoscopic features will help to obviate the need for skin biopsies in many doubtful cases. Methods: This was a descriptive study of 108 cases of classical lichen planus cases conducted at a tertiary care hospital in South India over a period of one year. Dermoscopic examination of the LP lesions were carried out using DermLite DL3N and histopathological samples were analyzed in 35 cases. Results: The dermoscopic features were blue globules in 100%, Wickham’s striae in 92.6% and comedo like openings in 49.1%. Vascular patterns were noted only in 13%. On correlating Wickham’s striae in dermoscopy with wedge shaped hyper granulosis on histopathology using the chi-square test we found agreement (kappa value 0.242). We also found that dermoscopy was 93.75% sensitive and 33.33% specific regarding Wickham’s striae in relation to wedge shaped hyper granulosis. In 85% of cases blue globules were present dermoscopically and dermal melanophages were found histopathologically. Conclusions: Wickham’s striae can be considered as a diagnostic dermoscopic finding in lichen planus whereas findings like bluish pigmentation and vascular structures depended on the skin colour of the patient. We also found agreement between dermoscopic and histopathologic features namely Wickham’s striae with wedge shaped hyper granulosis and blue globules with dermal melanophages.